Yeast genetics to dissect the nuclear pore complex and nucleocytoplasmic trafficking - Fabre, Emmanuelle; Hurt, Ed (Annual review of genetics, 1997)
▪ Abstract Eukaryotic cells evolved when their genetic information was packed into the cell nucleus. DNA replication and RNA biogenesis occur inside the nucleus while protein synthesis takes place in the cytoplasm. Bi-directional trafficking between these two compartments is mediated by a single supramolecular assembly, the nuclear pore complex. Nucleocytoplasmic transport is signal mediated, energy dependent, and requires, besides nuclear pore proteins (nucleoporins), a number of soluble transport factors. We review here our current knowledge on the role of nucleoporins, and on the mechanism of nucleocytoplasmic transport, with emphasis on the yeast Saccharomyces cerevisiae.